The Role of School Supervisors' Assistance and School Principals' Managerial Proficiency in Overcoming The Teachers' Quality and Competency Issues in SMK X Malang - Setiawan, Nuri Rizki; Sultoni, Sultoni (Universitas Negeri Malang, 2025)
Education has an important contribution to the development of human resources and the progress of civilization. In carrying out the education system and process, it requires involvement from various components, including the government, education services, supervisors, school principals, school committees and teachers. SMK X Malang City is a vocational school that has a role in providing services and education to the community. Based on the results of initial research and observations, the problem was found that the competence and quality of teachers in providing educational services was less than optimal. In responding to this, the role of school supervisors and school principals is needed in solving these problems. This research is a type of qualitative research that will produce descriptive data. The research method uses direct observation and literature study analysis. Based on the observation process and literature study, the author provides recommendations in the form of concrete stages in solving problems by involving the roles of school supervisors and school principals collaboratively. The explanation of problem solving includes, 1) Identifying competencies and qualities that need to be improved, 2) Analysis of the root of the problem, 3) Setting specific and measurable goals, 4) Development of training and professional development programs, 5) Implementation of coaching and mentoring programs, 6) Evaluation and regular feedback. At each stage, active commitment and collaboration is needed from the school principal, school supervisor and other parties in planning, implementing, monitoring and evaluating the achievement of each stage that has been determined. The hope is that by establishing these six problem solving steps, the competency and quality of teachers at SMK X Malang City will significantly improve and improve.